Efektivitas Penerapan Metode Make A Match Pada Pembelajaran Studi Fiqih Kelas XI Agama Di MA Unggulan KH. A. Wahab Hasbullah Tambakberas Jombang - Zakiyah Darojat (Universitas KH. A. Wahab Hasbullah, 2020)
The background of this research is the writer's interest in the methods used in the study of Fiqh studies and the importance of delivering the lesson well so that students more easily understand the lesson. Lately various methods have emerged that can make learning easier. Of course, the emerging methods offer their respective advantages in the learning process, with the results that will be obtained later. Starting from understanding, mastery of the material to the activeness of students.The Make A Match method is an alternative learning method that can be applied to students. The application of this method starts with a technique where students are told to look for pairs of cards which are answers / questions before the time limit students who can match the cards are given points.This research is a kind of quantitative descriptive field research, by taking the location of research in MA Featured KH. A. Wahab Hasbullah Tambakberas Jombang. Data collection is done by observation, interview, questionnaire, and documentation while the data analysis technique uses Mean (average) and Paired Sample t-test.The results of the research The effectiveness of the application of the Make A Match method in the study of Fiqh studies shows that the results of data analysis using the Paired Sample Test formula t-test produced a correlation value of 0.791 which is said to be in the category of high or strong correlations. With a significance value (2-tailed) is 0,000 with a sum of N = 25. Because 0,000 is less than 0.05, it can be stated as significant. So it can be concluded that the result is effective on student achievement in class XI Religion II MA Featured KH. A. Wahab Hasbullah Tambakberas Jombang if applying the Make A Match method in the subject of Fiqh.